Peran Fintech Dalam Meningkatkan Literasi Keuangan Usaha Mikro Kecil Menengah Di Batam - Dian Efriyenty (Jurnal Riset AKuntansi dan Bisnis, 2022)
Among the impacts that occur on online media, one of which is balance theft. The implementation of more advanced technology payments and consumers without having to incur much higher marketing or operational costs. The various objectives of the research are to see the phenomenon of financial literacy in the micro community. While the sample in this study was 154 MSMEs in the Batu Aji area. On February 2, 2022 at 13:00 WIB to Rafflesia UMK, Mandiri Waste Bank UKM and Snack and Cookies Bank, the research team conducted interviews related to financial literacy and fintech. Based on the survey results, there are still many among the micro community who do not understand online-based transactions. Even though the system makes it easier for MSME actors to transact without having to leave the house. Likewise, there are several MSME actors who have used fintech through several conventional banks.